SOSIALISASI PEMASARAN PRODUK UMKM SECARA ONLINE - Zaki Ainul Fadli; Fajria Noviana; Nur Hastuti (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2021)
UMKM is one of the pillars of the national economy. UMKM has great potential to continue to grow and develop despite the market trends that are starting to shift from offline to online. Therefore, it takes effort to provide ways and strategies to sell online. This community service was held with the aim to provide an understanding of the online marketing of UMKM products. The method used in online socialization is in the form of lectures, discussions, and questions about Online UMKM Product Marketing, which is divided into two sessions with two different subthemes: the first session with the title "UMKM in Pandemic Era: Why Should Online?" and the second session with the title "Successful in Selling With Whatsapp". The results of the activity showed that the participants followed enthusiastically and were interested in this socialization theme. The conclusion that can be drawn is the utilization of technology is very necessary for online marketing. In addition, the right marketing strategy is needed by utilizing social media optimally. Whatsapp is one of the media that is widely used by the people of Indonesia. By utilizing Whatsapp Business, we can easily promote UMKM products.